Les trames vertes pour les citadins : une appropriation contrastée à Marseille, Paris, Strasbourg - Sandrine Glatron; Étienne Grésillon; Nathalie Blanc (Développement Durable et Territoires)
What greenway can the city dwellers dream of ? Focus groups of city dwellers have been organized in three French cities whith very different urban culture and environmental context : Paris, Marseille and Strasbourg. The debates between the participants allowed us to evidence that what they imagine is part of an environmental esthetic and reveals a relationship with nature which are different from one town to another. Nevertheless, everywhere, urban dwellers’ representations of nature and natural continuities reveal the importance of senses. It seems usefull, then, to explore the field of environmental aesthetics that could lead us to think about how citizens could appropriate and participate to these new urban structures promoted by the so called French law “Grenelle II” de l’environnement).